التروك النبوية بين الاتباع والابتداع - تأصيلا وتطبيقا - قروي حورية; بن قومار لخضر (University of Elouedجامعة الوادي, 2024)
تعتبر التروك أحد قسمي السّنة النّبوية، وهو من المواضيع الحيّة التي لها صلة بواقع المسلمين، لا سيما مع كثرة المحدثات في حياة النّاس، بالإضافة إلى وقوع الاشتباه والالتباس فيه، ممّا أدّى إلى الابتداع في الدّين، وبما أن من أسس تبديع الأمور المستحدثة ترك النبي ، فإن هذا البحث يسعى إلى فهم التّروك النبوية وأقسامها، لأن ذلك يعين على فهم البدع وأنواعها، وكذا توضيح العلاقة التي تربطهما. وقد اختلف الفقهاء في صحّة إثبات الحكم الشرعي بالتّرك أو نفيه، فيكون التّرك حجّة، والمتروك محصورا في دائرة المحرّم فهو بدعة، أو ليس بحجّة ولا ينتج التّرك حكما فيكون دليلا على الجواز ورفع الحرج، أو التّفصيل في ضوء قواعد الشّريعة وأصولها، واختتم البحث بتوضيح أثر التروك النبوية في إبطال البدع بذكر بعض النماذج التي حكم عليها بعض العلماء ببدعيتها. The Turk is one of the two sections of prophetic Sunnah, which is a living topic of relevance to the reality of Muslims, especially with the abundance of novelties in people’s lives, as well as suspicion and confusion, which led to innovation in religion. Since one of the foundations of innovating new matters is what the Prophet Muhammad has abandoned, this research seeks to understand the prophet’s abandonments and its divisions because this helps to understand bid’ah and its types, as well as to clarify their relationship. Scholars disagreed concerning the validity of the legitimate provision by abandonment or denial, where abandonment can be evidence. The research concluded by clarifying the effect of prophetic abandonments in nullifying bid’ah by mentioning some models judged by some scholars of being bid’ah
Keywords: الأثر; العلاقة; الأحكام الشرعية; البدع المستحدثة; الترك; Impact; relationship; legal rulings; novelty; abandonment